Women`s Australian football: Sports science, strength and conditioning, injury prevention and drill development - what do we know? - Couvalias, G. (Journal of Australian Strength and Conditioning, 2019)
Elite women`s Australian Football players cover greater relative high-speed, very-high-speed and sprint distances than sub-elite and are at 9.2 greater risk of ACL injury than elite males. Better understanding of match-running allows integration of targeted running and injury prevention programs.